2023
DOI: 10.3390/foods12163013
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical and Nutritional Properties of Chia Seeds from Latin American Countries

Natalia Vera-Cespedes,
Loreto A. Muñoz,
Miguel Ángel Rincón
et al.

Abstract: In the last few decades, chia (Salvia hispanica L.) cultivation has expanded around the world, and the seeds have become well known due to their rich composition of nutrients and bioactive compounds. The aim of this work was to evaluate the physical, chemical, and nutritional profile of eight types of chia seeds grown in different Latin-American countries (Argentina, Bolivia, Chile, Ecuador, Mexico, Paraguay, and Peru). The results showed that several nutritional parameters of the seeds, such as the protein co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…In contrast, Goyat et al reported that the product contains as much as 692.91 ± 1.39 mg/100 g 20 . This is also confirmed by other studies, where the range of Ca concentrations is wide, from 460 to 671 mg/100 g 21 , 22 . In second place in terms of calcium content is flax (Table 1 ) 252.85 mg/100 g, which is in line with the values determined by the USDA and others (220–380 mg/100 g) 19 , 21 , 23 , 24 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, Goyat et al reported that the product contains as much as 692.91 ± 1.39 mg/100 g 20 . This is also confirmed by other studies, where the range of Ca concentrations is wide, from 460 to 671 mg/100 g 21 , 22 . In second place in terms of calcium content is flax (Table 1 ) 252.85 mg/100 g, which is in line with the values determined by the USDA and others (220–380 mg/100 g) 19 , 21 , 23 , 24 .…”
Section: Resultssupporting
confidence: 90%
“…Flax flour contains the most magnesium, i.e. 590.75 mg/100 g, followed by chia 499.2 mg/100 g (Table 1 ), and according to literature data there are lower Mg contents for flax from 350 to 431 mg/100 g 21 , 24 and respectively for chia from 250 to 322 mg/100 g 19 , 21 , 22 . Buckwheat and almond flour are unusually rich in magnesium, as the concentrations of this element in the products were 233 and 229.8 mg/100 g, respectively (Table 1 ), a result similar to the 219 mg/100 g reported by Kunachowicz for buckwheat and 239 mg/100 g for almonds 26 .…”
Section: Resultsmentioning
confidence: 69%
“…This may be due to the fibrous material characteristic of obovoidal to ellipsoidal shape with a rounded base and apex of chia seeds. When it was processed (ground), the irregular shape became a characteristic of the powder with many fibrous furrows remaining [13]. The characteristics of pharmaceutical powders are essential to determine the specifications and ensure that they follow the product batch to batch.…”
Section: Particle Size Of Quinoa and Chiamentioning
confidence: 99%
“…However, for the development of formulations containing quinoa, it is necessary to extract saponins from the grains, due to the bitter residue in the oral mucosa [12]. On the other hand, chia has a pleasant sweetness in 2 contact with water or in the presence of any other food and the high nutritional value of this seed can be complemented if incorporated into a formulation containing quinoa [13].…”
Section: Introductionmentioning
confidence: 99%
“…For the development of formulations containing quinoa, it is necessary to extract saponins from the grains to prevent the formation of bitter residues in the oral mucosa after consumption [18]. On the other hand, chia has a pleasant sweetness when it is in contact with water or in the presence of any other food, and the high nutritional value of this seed can be complemented if it is incorporated into a formulation containing quinoa [19].…”
Section: Introductionmentioning
confidence: 99%